2020
DOI: 10.1002/jimd.12297
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the clinical spectrum of isolated methylmalonic acidurias: cblA and mut

Abstract: Introduction Long‐term outcome is postulated to be different in isolated methylmalonic aciduria caused by mutations in the MMAA gene (cblA type) compared with methylmalonyl‐CoA mutase deficiency (mut), but case definition was previously difficult. Method Cross‐sectional analysis of data from the European Registry and Network for Intoxication type Metabolic Diseases (Chafea no. December 1, 2010). Results Data from 28 cblA and 95 mut patients in most cases confirmed by mutation analysis (including 4 new mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Mut À and cblB patients had intermediate phenotypes, while B 12 -responsive cblA subjects had the best long-term prognosis. 31 Large patient registries have confirmed the earlier observations on the importance of the underlying genetic and enzymatic defect on disease mortality, morbidity, and multisystem complications 40,44,46 and have helped evaluate older and newer biomarkers against molecular, biochemical, and clinical severity scores. 5,8,39,47,51,80 Multiomics profiling of over 200 patient fibroblast lines allowed a powerful integrated analysis of whole genome and transcriptome sequencing, data-independent acquisition mass spectrometry proteotyping, and metabolomics that enabled novel associations of various biomarkers with cell phenotypes and clinical severity scores.…”
Section: Enzyme Activity In Vitromentioning
confidence: 76%
See 2 more Smart Citations
“…Mut À and cblB patients had intermediate phenotypes, while B 12 -responsive cblA subjects had the best long-term prognosis. 31 Large patient registries have confirmed the earlier observations on the importance of the underlying genetic and enzymatic defect on disease mortality, morbidity, and multisystem complications 40,44,46 and have helped evaluate older and newer biomarkers against molecular, biochemical, and clinical severity scores. 5,8,39,47,51,80 Multiomics profiling of over 200 patient fibroblast lines allowed a powerful integrated analysis of whole genome and transcriptome sequencing, data-independent acquisition mass spectrometry proteotyping, and metabolomics that enabled novel associations of various biomarkers with cell phenotypes and clinical severity scores.…”
Section: Enzyme Activity In Vitromentioning
confidence: 76%
“…Mut − and cblB patients had intermediate phenotypes, while B 12 ‐responsive cblA subjects had the best long‐term prognosis 31 . Large patient registries have confirmed the earlier observations on the importance of the underlying genetic and enzymatic defect on disease mortality, morbidity, and multisystem complications 40,44,46 and have helped evaluate older and newer biomarkers against molecular, biochemical, and clinical severity scores 5,8,39,47,51,80 …”
Section: Enzymatic Activitymentioning
confidence: 78%
See 1 more Smart Citation
“…For MMA it has been shown that the genetic cause of the condition directly affects the long‐term clinical outcome, where the severe MMUT‐deficient cases (termed mut 0 ) show the highest excretion of urinary methylmalonic acid which is directly correlated to the likelihood of developing chronic kidney disease in the long term 70 . Patients can be further segregated by classifying them into categories of increasing severity, ranging from mut 0 (loss of enzymatic function of MMUT) to cblB , to mut − (MMUT defect with some residual activity) and cblA , where the latter two show more attenuated disease courses including a lower rate of kidney and neurocognitive complications 70–72 …”
Section: Impact Of Biochemical Subtypes and Implications For Treatmentmentioning
confidence: 99%
“…This knowledge is of relevance for the optimization of the diagnostic process, patient clinical paths, healthcare planning, and counselling of parents having a child with a rare disease. For example, comparative phenotyping helped to identify the need to carefully monitor renal function not only in individuals with isolated methylmalonic acidurias but also in individuals with other organic acidurias such as propionic aciduria and glutaric aciduria type 1 ( 24 , 38 ) since chronic kidney dysfunction was already well known in methylmalonic aciduria ( 39 , 40 ), but was underestimated in propionic aciduria and unknown in glutaric aciduria type 1 before. Patient registries also allow comparison between different diagnostic journeys and related health outcomes on an international level, especially if there are known rigid differences in diagnostic approaches between countries, that may be evaluated against each other, as is the case with differing national newborn screening panels.…”
Section: Patient Registries Are Multi-purpose Instruments For Rare Di...mentioning
confidence: 99%